Activation of Trifluoromethylthio Moiety by Appending Iodonium Ylide under Copper Catalysis for Electrophilic Trifluoromethylation Reaction. Issue 5 (8th March 2016) - Saidalimu, Ibrayim; Suzuki, Shugo; Tokunaga, Etsuko; Shibata, Norio
Abstract: A novel iodonium‐ylide compound2 that appends atrifluoromethylthio (SCF3 ) group is disclosed as a new, shelf‐stable electrophilic trifluoromethylation reagent. Unlike known shelf‐stable electrophilic trifluoromethylation reagents, 2 has a stable SCF3 group which is activated by appending iodonium ylide under copper catalysis via sulfonium ylide to generate a cationic trifluoromethyl (CF3 ) species. Reagent2 was found to be an efficient electrophilic trifluoromethylation reagent for a wide range of silyl enol ethers3 under copper catalysis. Cyclic and acyclic α ‐trifluoromethyl ketones4 were obtained by reagent2 in moderate to good yields. On the other hand, a difluoromethylthio analogue5 did not affect intermolecular transfer difluoromethylation to substrates. Instead, intramolecular 1, 4‐migration proceeded similar to the Stevens rearrangement to provide6 in 21% yield, independent of the presence of nucleophiles3 . Abstract : In situ‐activation of SCF3 to +CF3 . Unlike known electrophilic trifluoromethylation reagents, the new reagent2 has a stable SCF3 group which is activated by appending iodonium ylide under copper catalysis via sulfonium ylide to generate a cationic CF3 species for intermolecular transfer trifluoromethylation. On the other hand, a difluoromethylthio analogue5 does not affect intermolecular transfer difluoromethylation, but intramolecular 1, 4‐migration proceeded to a Stevens rearrangement product6 .